The rapid degradation of Lambda-Cyhalothrin makes treated vegetables relatively safe for consumption - Djouaka, R.; Soglo, M.; Kusimo, M.O.; Adéoti, R.; Talom, A.; Zeukeng, F.; Paraïso, A.; Afari-Sefa, Victor; Saethre, M.G.; Manyong, Victor M.; Tamò, Manuele; Waage, Jeff; et al. (MDPI, 2018)
Lambda-cyhalothrin (λ-cyhalothrin) is the most commonly used pyrethroid insecticide for vegetable farming in Benin. This insecticide is misused and overused by farmers, and hence may pose health hazards to consumers. We monitored λ-cyhalothrin residues in lettuce and cabbage from farms at the market gates in Cotonou and Parakou using high performance liquid chromatography (HPLC) analysis techniques. These residues were also monitored on samples directly from farms (on-farm sampling) for 14 days post-treatment. Potential factors such as photolysis and hydrolysis involved in λ-cyhalothrin degradation were also screened. Results revealed that the level of λ-cyhalothrin residue concentrations in lettuce from Houeyiho decreased from 4.2 mg/kg on Day 1 to about 0.2 mg/kg on Day 7. On Day 9, analyzed lettuces were all λ-cyhalothrin free. In contrast, even 14 days after treatment of cabbage from Bawera (Parakou), we still recorded the presence of λ-cyhalothrin residues in analyzed samples. For samples from market gates, λ-cyhalothrin residues were found in lettuce from two markets out of the nine surveyed in Cotonou. Interestingly, none of these contaminated samples had residues above the maximum residue limit for lettuce (MRL = 0.5 mg/kg). Similarly, in Parakou, samples from all five surveyed vegetable markets were contaminated with λ-cyhalothrin residues at concentrations below the MRL for cabbage (MRL = 0.2 mg/kg). We conclude that λ-cyhalothrin residues in lettuce and cabbage from farms and markets in Parakou and Cotonou are within the MRL, and hence are relatively safe for consumption.